Association of Baseline Frailty Status and Age With Postoperative Complications After Cochlear Implantation: A National Inpatient Sample Study. Issue 10 (3rd December 2022) - Cole, Kyril L.; Babajanian, Eric; Anderson, Ryan; Gordon, Steve; Patel, Neil; Dicpinigaitis, Alis J.; Kazim, Syed Faraz; Bowers, Christian A.; Gurgel, Richard K.
Abstract : Objective: To conduct a national registry-based evaluation of the independent associations of chronological age and frailty, as measured by 5- and 11-factor modified frailty index (mFI-5, mFI-11) score, on postoperative outcomes of participants undergoing cochlear implantation (CI). Study Design: Cross-sectional analysis. Setting: Multicenter national database. Participants: Adults 18 years or older who underwent CI during 2001 to 2018. Main Outcome Measures: Any postoperative complications (determined as the presence of major, minor, or implant-specific), extended hospital length of stay (eLOS) (≥75th percentile of study population), and nonhome discharge destination. Results: There were 5, 130 participants included with a median age of 60 years (interquartile range, 44–73 y) and slight female predominance (53.5%). Under mFI-5 scoring, there were 2, 979 (58.1%) robust (mFI-5 = 0), 1710 (33.3%) prefrail (mFI-5 = 1), 362 (7.1%) frail (mFI-5 = 2), and 78 (1.5%) severely frail (mFI-5 ≥ 3) participants. Three hundred twenty-eight (6.49%) participants experienced a postoperative complication, with 320 (6.2%) discharged to a nonhome destination. Multivariate analysis showed no statistically significant correlation between increasing participant age or frailty status and postoperative complications; however, increasing baseline frailty tier showed an independent association with risk of eLOS (severely frail: odds ratio, 4..83; 95% confidence interval, 3.00–7.75; p < 0.001) and nonhome discharge (severely frail: odds ratio, 6.51; 95% confidence interval, 3.81–11.11; p < 0.001). The mFI-11 showed very similar trends. Conclusion: Among those evaluated, this study demonstrates that CI is a low-risk procedure in participants of all ages. Increasing frailty does not predispose to postoperative complications. However, frail patients are at additional risk for an eLOS and nonhome discharge. Short follow-up time, hospital-coding errors, and selection bias of more robust patients may limit the true results of this study.